(untitled) (Jurnal Bina Praja, 2021)
The Indonesian e-Government index for 2020 is internationally ranked 88, up 19 points from the previous ranking of 107 in 2018. This increase results from e-Government implementing agencies and an increase in public participation and contributions from research institutions. It always contributes to e-Government issues theoretically and practically. The results of studies related to the implementation of e-Government are also needed to answer the current problems and become a reference of e-Government development following Indonesian conditions. This study explores the studies that have been carried out during the last five years using the perspective of Indonesia’s e-Government Ranking (PeGI), namely the dimensions of policy, institutional, application, infrastructure, and planning. The study used a literature review method with data sources obtained on the Garuda Ristek portal BRIN-Indonesian Publication Index. The number of articles collected was 45 articles which were then grouped based on the PeGI dimension, research methods, and types of e-Government relations. The results show that the perspective of the dimensions of the Indonesian e-Government Ranking can be a reference to see a picture of the conditions of e-Government implementation and the influencing factors. Furthermore, studies related to e-government issues can provide input information and recommendations for solutions to e-Government administrators. Therefore, it is necessary to increase the number of studies on e-Government in Indonesia supported by the government and related institutions to improve the quality of Indonesian e-Government.